Bioinformatics for Personalized Medicine 10th Spanish Symposium, JBI 2010, Torremolinos, Spain, October 27-29, 2010. Revised Selected Papers - Freitas, Ana T.; Navarro, Arcadi; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the refereed proceedings of the 10th Spanish Symposium on Bioinformatics, JBI 2010, held in Torremolinos, Spain, in October 2010. The 13 revised full papers presented were carefully reviewed and selected from numerous submissions. The papers are structured in topical sections on next-generation sequencing data; genome-wide association studies; high-performanced databases; text-mining; tools for integration of Web services; ontologies; analysis and visualization of omics data.
Keywords: Computer science; Computer Communication Networks; Database management; Data mining; Information storage and retrieval systems; Bioinformatics; Computer Science; Computational Biology/Bioinformatics.; Information Systems Applications (incl. Internet).; Information Storage and Retrieval; Database Management; Computer Communication Networks; Data Mining and Knowledge Discovery